Environmental risk factors and genetic markers of Kaposi's sarcoma‐associated herpesvirus infection among Uygur population in Xinjiang, China. Issue 6 (26th January 2022) - Zhang, Xin; Fang, Qiwen; Zhu, Sibo; Wu, Xuefu; Yuan, Huangbo; Liu, Zhenqiu; Xu, Yiyun; Chen, Tao; Zeng, Yan; Zhang, Tiejun
Abstract: Kaposi sarcoma‐associated herpesvirus (KSHV) is endemic in Xinjiang, China. Determinants of KSHV seropositivity among high‐risk groups are not well understood. We seek to identify genetic and environmental predisposing factors for KSHV infection among Uygurs in this endemic region. A cross‐sectional study was performed among the Uygur population in Xinjiang, China. KSHV‐antibodies were detected using immunofluorescence assay (IFA) and human leukocyte antigen ( HLA ) alleles were genotyped. Univariate and multivariate logistic regression analyses were applied to explore the environmental and genetic risk factors of KSHV seropositivity. Finally, a total of 721 participants were included. The seroprevalence of KSHV was 24.1% among this population. Sweet‐food preference (odds ratio [OR] 1.85, 95% confidence interval [CI] 1.03–3.34), and coronary heart disease (OR 1.91, 95%CI 1.24–2.94) were statistically correlated with KSHV infection. HLA‐DQB1*06:09 were found to significantly increase the risk of KSHV infection under all 3 models (ORAllelic  = 4.06; ORDominant  = 3.27; and ORRecessive  = 8.06). Six SNPs (SNP0260, SNP0361, SNP0797, SNP0852, SNP1159, and SNP1375) in the DQB1 and DRB1 region and haploid type GTCTAACTAATC in block 17 were statistically associated with KSHV infection. We demonstrated that genetic variations in HLA‐DQB1/DRB1 and environmental risk factors were strongly associated with KSHV infection among this population. Key Points/Highlights: Identifying potential predisposing factors of Kaposi sarcoma‐associated herpesvirus (KSHV) seropositivity in endemic settings, such as the Uygur population in Xinjiang, China, may be useful for the development of both therapeutic and preventive strategies of KSHV/KS to address this important public health concern. Susceptibility to KSHV infection might be caused by virus‐host‐environment interactions, HLA gene polymorphisms may play a crucial role in controlling the immune response to KSHV infection. Sweet‐food preference and coronary heart disease were significantly correlated with KSHV seropositivity. HLA‐DQB1*06:09, six SNPs, and haploid type GTCTAACTAATC in block 17 may be associated with KSHV infection. The first study to investigate the relationship between environmental risk factors, HLA gene polymorphisms, and KSHV susceptibility among Uygur ethnic population in Xinjiang, providing empirical data for further in‐depth and extensive studies. And the findings will contribute to an enhanced awareness of KSHV infection among high‐risk populations and benefit the prevention of KSHV in countries facing the same situations.